Closed-chest robotic repair of mitral prolapse. Surgical technique and early results - Sandoval, Elena; Morales-Rey, Ignacio; Bartolozzi, Luis; Pereda, Daniel (Frontiers in Cardiovascular Medicine, 2023)
Background: Robotic mitral repair is generally performed with four intercostal trocars and a minithoracotomy. We describe our technique and results with a totally-thoracoscopic closed chest approach using a 12mm valveless trocar as "working port', without a minithoracotomy. We compared our results with this technique with a control group of robotic mitral repairs performed earlier with a minithoracotomy. Methods: Review of all patients with degenerative mitral valve disease who underwent robotic mitral valve repair surgery since December 2019 (n=110). Patients with concomitant procedures (n=8) were excluded. The remaining 102 patients were divided in two groups, depending on the approach used, minithoracotomy (n=63) and totally thoracoscopic (n=39).Results: There were no significant differences between groups regarding preoperative characteristics. All procedures were completed robotically as planned, and repair rate was 100%. The minithoracotomy group showed a higher percentage of leaflet resections (17,9% vs 38,7%; p=0,03). All surgical times were significatively reduced in the totally thoracoscopic group: Cardiopulmonary bypass (97 vs. 115min, p=0,0008), ischemic time (67 vs. 80min, p=0,0013) and total surgical time (185 vs. 225 min; p<0,00001). There were no differences in ICU length of stay (1 day, p=0,07) but hospital length of stay was shorter in the totally thoracoscopic group (4 days; p=0,0001). Postoperative complications were similar between groups. MR at discharge was mild or less in all cases.Conclusions: Robotic mitral repair for degenerative disease can be safely performed as a closed-chest procedure, using a 12mm trocar as "working port" and avoiding the need for a minithoracotomy. This approach does not seem to negatively affect the quality of the procedure by any measure, providing similar excellent clinical outcomes and repair rate. All surgical times were shorter in the closed-chest group.